Feingold syndrome type 2 in a patient from China. Issue 7 (5th April 2021) - Lei, Jie; Han, Luhao; Huang, Yanke; Long, Min; Zhao, Gang; Yan, Shida; Zhang, Jing
Abstract: Feingold syndrome type 2 (FGLDS2, MIM614326) is a genetic congenital malformation syndrome, caused by germline heterozygous deletion of MIR17HG on chromosome 13q31, which is extremely rare worldwide. To date, less than 25 patients have been described in the literature. Here, we report on a 3‐year‐old girl presented with hip dysplasia, polysyndactyly of the left thumb, brachymesophalangy of the fifth digit, microcephaly, intellectual disability, and growth delay. This is likely to be the first case of Feingold syndrome type 2 ever discovered among Chinese population. Through genetic testing and pedigree analysis, she was identified to have a de novo 4.8‐Mb microdeletion at chromosome 13q31.3‐q32.1, encompassing MIR17HG, GPC5, and GPC6 . Additionally, we detected two common compound heterozygous variants (c.919‐2A>G and c.147C>G) in SLC26A4 encoding pendrin protein, as well as a novel heterozygous variant c.985_988del in COMP encoding cartilage oligomeric matrix protein. This case report aims to analyze the microdeletion and the three types of variant detected in the patient, and to explore the association between the genotype and phenotype in patients with Feingold syndrome type 2, which may contribute to further understanding and future diagnosis of this disorder.